The Regional Development Assessment of Social Resilience Based on Quantifiable Analyses Apply to Guangfu Village - Tung Wu, Chao; Ting Shen, Yang (European Journal of Sustainable Development, 2019)
This research aims to analyze an organization‘s social impact under Social Resilience issue (Herb, 2005) by developing the regional development assessment based on ESG standard. In addition, the assessment is also related with Sustainable Development Goal No.11 (Sustainable cities and communities). The application context is using our regional development assessment to evaluate how an organization can interfere when a community suffers external disturbances. This content could be established a sustainable management to arrange concrete consequences from various aspects of perspectives. It is observed that the assessment indicates that how to evaluate social impact of organizations in the community and scientifically quantitate value for Social Resilience. The framework is based on ESG consisting of Environment, Social, and Governance. This estimate proceeds from testing a non-governmental organization (NGO) or a non-profit organization (NPO) interfering with the regions results in how much their influence is and how large a range of their influence is. The assessment was applied to analyze the region—Guangfu Village in Taichung City, Taiwan. The evaluation was not really phenomenal on the appearance under ESG standard. According to this study, the consequences from the assessment are described as below. Keywords: Social Resilience; ESG; Sustainable Development Goal